Characteristics of the Onset and Evolution of Juvenile Rheumatoid Arthritis Symptoms during the First Year of its Development - I.S. Lebets; N.O. Panko; O.V. Matviienko; Ye.M. Zaitseva; N.S. Shevchenko (Zaslavsky O.Yu., 2015)
The article presents the data about early symptoms of juvenile rheumatoid arthritis in comparison with the reactive arthritis. Description of the articular syndrome is provided, the incidence of isolated joints affection and radiologic abnormalities in them were analyzed. The designed algorithm for differential diagnosis of juvenile rheumatoid and reactive arthritis is presented.